1976
DOI: 10.1007/bf00215880
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural alterations in skeletal muscle fibers of streptozotocin-diabetic rats

Abstract: The ultrastructure of fast-twitch-oxidative-glycolytic (FOG), fast-twitch-glycolytic (FG) and slow-twitch-oxidative (SO) fibers in plantaris and soleus muscles of normal and streptozotocin-diabetic rats was studied. In the diabetic animals, the mitochondria of FOG and SO fibers showed a loss of cristae and an increase in electron-dense granules. There was also an increased number of lipid droplets in close proximity to the mitochondria and the nuclei, and a separation of individual muscle nuclei to form satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
7
24
0
Order By: Relevance
“…The relaxation deficit shown by HRT measures suggests that SR Ca2" sequestration may also be impaired. Morphological studies provide evidence that SR and T tubules are disrupted in skeletal and cardiac muscle of diabetic rats (Chao et al 1976;Afzal, Ganguly, Dhalla, Pierce, Singal & Dhalla, 1988). In vitro studies of heart (Penparkgul, Fein, Sonnenblick & Scheuer, 1981;Ganguly et al 1983) and skeletal muscle (Eibschutz et al 1984) demonstrated reduced SR Ca2+-ATPase activity, although this has been disputed for skeletal muscle (Ganguly, Mathur, Gupta, Beamish & Dhalla, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxation deficit shown by HRT measures suggests that SR Ca2" sequestration may also be impaired. Morphological studies provide evidence that SR and T tubules are disrupted in skeletal and cardiac muscle of diabetic rats (Chao et al 1976;Afzal, Ganguly, Dhalla, Pierce, Singal & Dhalla, 1988). In vitro studies of heart (Penparkgul, Fein, Sonnenblick & Scheuer, 1981;Ganguly et al 1983) and skeletal muscle (Eibschutz et al 1984) demonstrated reduced SR Ca2+-ATPase activity, although this has been disputed for skeletal muscle (Ganguly, Mathur, Gupta, Beamish & Dhalla, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative capacity was reported to be reduced by diabetes in mixed skeletal muscles (Armstrong et al 1975). A morphological correlate may be decreased mitochondrial density and disruption of their cristae in skeletal and cardiac muscle (Chao et al 1976;Afzal et al 1988). This could explain reduced soleus SDH staining, which may contribute to increased fatiguability if ATP for contraction was limited.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial disruption, including loss of cristae, has been noted in the SO and FOG fibres of rat soleus and plantaris muscle (Chao et al 1976). In the present study, the marked disruption of SDH staining in soleus muscle also implies an impairment of oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle mitochondria of insulin-deficient rats made diabetic with the b-cell toxin streptozotocin, thereby mimicking type 1 diabetes, showed a loss of cristae and an increase in electron-dense granules along with lipid droplets around the mitochondria (59). Studies using alloxan to damage b cells and induce diabetes in rats revealed a decrease in mitochondrial number in liver and heart, with mitochondrial swelling and damage to mitochondrial membranes and cristae (209).…”
Section: Type 1 and Type 2 Diabetesmentioning
confidence: 99%